The 'how' of learning. (2nd December 2019) - Rawstrone, Annette
Abstract : Most parents have heard of the Early Years Foundation Stage (EYFS) but it is also important to be familiar with the Characteristics of Effective Learning (CoEL) which are integral to it. Annette Rawstrone provides the first of a four part guide.